La violence contre l’épouse, un crime passionnel - Wilson, Margo; Daly, Martin (Criminologie, 1996)
Two Statistics Canada data sources provide case information on violence against Canadian wives : the "Homicide Survey", an archive of all homicides known to police since 1974, and the 1993 national telephone "Violence against Women Survey". When combined with population-at-large information, these sources illuminate risk patterns for lethal and nonlethal violence, which are similar in most, but not all, particuliars. Rates of both lethal and nonlethal violence against wives vary in relation to age, registered versus common law status, separation, and autonomy-limitating behaviour by the husband. These risk patterns are discussed in relation to factors affecting the intensity of male sexual proprietariness. Risk patterns in Quebec parallel those for Canada as a whole in most, but not all, particulars.